1998
DOI: 10.1097/00000658-199810000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Compression in the Thoracic Outlet

Abstract: Of more than 15,000 patients evaluated for TOS, 3914 underwent primary neurovascular decompression procedures and 1221 underwent second surgical procedures for recurrent symptoms. Of 2210 consecutive patients, 250 had symptoms of upper plexus compression only (median nerve), 1508 had symptoms of lower plexus compression only (ulnar nerve), and 452 patients had symptoms of both. Ulnar and median nerve conduction velocities confirmed the clinical diagnosis. Transaxillary first rib removal alone for neurovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
133
0
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(147 citation statements)
references
References 20 publications
1
133
0
13
Order By: Relevance
“…It has been found that such dilated segments of the artery returns to normal dimension over time once the proximal stenotic element has been removed. 5,6 However, we do perform surgical repair of the aneurysmal SCA whenever indicated. Aneurysmorrhaphy is our most common strategy although venous or prosthetic interposition grafting is also performed in appropriate cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that such dilated segments of the artery returns to normal dimension over time once the proximal stenotic element has been removed. 5,6 However, we do perform surgical repair of the aneurysmal SCA whenever indicated. Aneurysmorrhaphy is our most common strategy although venous or prosthetic interposition grafting is also performed in appropriate cases.…”
Section: Discussionmentioning
confidence: 99%
“…One disadvantage of transaxillary intervention is that congenital fibromuscular bands are hard to see and arterial reconstruction is difficult, when required (3). One important complication of transaxillary approach surgery is the 20% recurrence rate (23,24). The main complications of transaxillary surgery include superficial and deep infections, pneumothorax, vascular injuries and neural damage.…”
Section: Discussionmentioning
confidence: 99%
“…by first rib resection (Zimmermann et al, 1981;Becker et al, 1983;Machleder, 1993;Urschel & Razzuk, 1998). Some investigators recommend such an invasive approach routinely e.g in patients with effort related thrombosis (Paget von Schroetter´s syndrome) (Kommareddy et al, 2002).…”
Section: Treatmentmentioning
confidence: 99%